7. DOCTRINE TESTING FROM A COMPLEX SYSTEMS PERSPECTIVE CONVENTIONAL VERSUS CONTEMPORARY APPROACHES IN THE AXIOM-BASED DOCTRINE TESTING MODEL AND SYSTEM RESILIENCE - Farrid Hidayat; Suroso; Kurniawan; Hidayad; Muchammad; Tutikurniadinda; Rickydika; Faried (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to methodologically analyze the limitations of conventional doctrine testing approaches and compare them with contemporary complex systems-basedapproaches, using doctrinal axioms and system resilience as the basis for evaluation.Operational doctrine is traditionally tested through conventional approaches that emphasizenormative compliance, historical precedent, and limited scenario-based simulations. Thisapproach is based on the assumption of strategic and operational environmental stability andthe linearity of cause-and-effect relationships. However, the dynamics of contemporarystrategic and operational environments which are non-linear, adaptive, and produce emergenteffects demonstrate a methodological gap between the reality of the system encountered andthe doctrine testing mechanisms employed. The study uses a conceptual qualitative approachthrough a systemic-doctrinal analysis with a comparative method of epistemic assumptions,testing logic, and validity criteria of both approaches. The analysis shows that the conventionalapproach is prone to pseudo-validity because it assesses doctrine primarily based onprocedural compliance, rather than systemic resilience to environmental change andoperational disruption. In contrast, the contemporary approach offers a more structurallyconsistent evaluation framework in addressing the complexity of the strategic and operationalenvironment. Therefore, doctrine testing needs to be reoriented from a normative verificationmodel to a complex systems-based evaluation model as a structural methodological necessity.This research contributes to the development of a doctrine evaluation methodology that is morerelevant to the study of contemporary defense doctrine and strategy.